1975
DOI: 10.1071/sr9750069
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extractable sulpher and potassium levels in soil due to oven drying and storage

Abstract: Appreciable increases in 'available' sulphur were noted for six soils from South Gippsland after oven drying at 40�C. Oven dried soils stored at room temperature or 3�C for periods of up to 12 months showed significant increases in sulphur extractable with calcium phosphate but not in sulphur levels extractable with charcoal plus calcium phosphate. Application of toluene as a bacteriostatic agent failed to stop increases in levels of sulphur extractable with calcium phosphate, although the magnitude of the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

1976
1976
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…Para cálcio e magnêsio,_M0LL0Y & LOCKMAN (1979) encontraram uma pequena variação, sendo que no presente trabalho verificou-se uma grande estabilidade destes elementos nos dois solos.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Para cálcio e magnêsio,_M0LL0Y & LOCKMAN (1979) encontraram uma pequena variação, sendo que no presente trabalho verificou-se uma grande estabilidade destes elementos nos dois solos.…”
Section: Resultsunclassified
“…Os resultados obtidos para o fósforo concordam com o encontrado por PISKULA (1971) que mostrou a influencia da secagem proporcionando um aumento na disponibilidade do elemento, porem nao constatou efeito do armazenamento após 3 a 5 meses. 0 trabalho de GUPTA & RORISON (1974) mostrou que o armazenamento foi um fator que influiu no teor de fósforo, com um aumento significativo sobre a disponibilidade do elemento para amostras armazenadas, semelhante ao obtido no presente trabalho com as amostras secas em estufa a 60°C, ate os 16 dias de armazenamento, e confirmando o trabalho de MOLLOY & LOCKMAN (1979), onde os autores demonstraram que a temperatura afeta positivamente o teor de fósforo.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…A secagem levou a um aumento do teor de potássio (ATTOE, 1946;HANWAY & SCOTT, 1957;PISKULA, 1971;GUPTA & RORISON,1974). Segundo Reitemeir (1951), se observa a diminuição no teor de potássio com a variação de temperatura e em outros trabalhos não foi observado diferença alguma em relação ao resultado do potássio (JAIYEBO, 1968;PEVERILL et al, 1975). Acredita-se que as variações observadas possam ser recorrentes da presença de diferentes minerais de argila encontrados nos solos.…”
Section: Methodsunclassified
“…Several investigators (Barrow, 1961;Freney, 1958;Peverill et al, 1975) have indeed found that drying of soil often leads to a release of SO4, presumably from organic matter. However, when the drying temperature is around 50°C the quantities of SO4 thus released will remain small.…”
Section: A P Values In Soil Extractsmentioning
confidence: 99%